Exploring the Safewards Programme to Reduce Restrictive Practices in Residential Aged Care: Protocol for a Pilot and Feasibility Study - Suzanne Dawson; Candice Oster; Michael Page; Stacey George (Wiley, 2024)
ABSTRACT Introduction Restrictive practice use in residential aged care homes internationally is unacceptably high. Although policies and legislation mandate the reduction or elimination of restrictive practices, there remains a gap in knowledge regarding strategies that have been effective in achieving a sustained reduction in restraint use. There is an urgent need to identify effective and feasible interventions that aged care staff can implement in everyday practice to reduce restraint use. Safewards is an evidence‐based programme that has demonstrated effectiveness in reducing conflict and restrictive practice use in inpatient psychiatric settings and has the potential to address the issue of restraint use in aged care homes. This study aims to evaluate the feasibility of Safewards in reducing restrictive practices in residential aged care homes. Methods This pilot and feasibility study will adopt a mixed methods process and outcomes evaluation. Safewards will be implemented in two Australian residential aged care homes. The Reach, Effectiveness, Adoption, Implementation and Maintenance framework will be used to evaluate implementation outcomes. Additionally, the Consolidated Framework for Implementation Research will be used to guide qualitative data collection (including semi‐structured interviews with residents/family members, aged care leaders and staff) and explain the facilitators and barriers to effective implementation. Conclusion This study will provide pilot evidence on the feasibility of the Safewards programme in residential aged care homes. Understanding the processes and adaptations for implementing and evaluating Safewards in residential aged care will inform a future trial in aged care to assess its effectiveness. More broadly, the findings will support the implementation of an international aged care policy of reducing restrictive practices in residential aged care. Patient or Public Contribution A person with lived experience of caring for someone with dementia is employed as a Safewards facilitator and is a member of the steering committee. Residents and family members will be invited to participate in the project steering committee and provide feedback on their experience of Safewards. Trial Registration ACTRN12624000044527.